Dampak Buruk Stunting Bagi Anak pada Usia Golden Age di Desa Pasiran Kecamatan Sei Dadap Kabupaten Asahan - Diva Genefa Andini Hrp; Catur Aldiansyah; Nurlatifah Manurung; Rahima Husna; Tetty Marlina Tarigan (Universitas Batanghari Jambi, 2023)
Stunting is a condition where a child's height is shorter than a child of the same age, with a Z-score for height for age (TB/U). Based on the standard of growth reached less than -2 standard deviation (SD). Poor nutrition during the first 1000 days of life causes growth retardation in children. Affected children have permanent physical developmental disabilities that affect their ability to work. The average IQ of retarded children is 11 points lower than the average IQ of children in the general population. The research method used in this research is a systematic review of published literature from national and international publications. The object of this research is in Pasiran Village, Sei Dadap District, Asahan Regency. The results of this study reveal that children who experience stunting in the first 2 years of life are at risk of having an IQ of 4.57 and a nonverbal IQ of less than 89.